Castlemans Disease - A Rare Cause of Pyrexia of Unknown Origin (PUO): Case Report (Bangabandhu Sheikh Mujib Medical University Journal, 2010)
Pyrexia of unknown origin (PUO) is a common problem in medical practice. Patients suffer from fever for long period but initial relevant investigations remain normal. Infection is the most common cause of PUO in developing countries. Other causes are lymphoma, myeloma, connective tissue diseases (CTD), sarcoidosis and malignancy etc. In our country, where no cause can be identified, a usual practice is to start anti-tubercular drugs. We report a patient who was suffering from prolonged fever and usual investigations were within normal limit except high erythrocyte sedimentation rate. In spite of having 6 months anti-tubercular drugs, the patient did not respond. Thorough examination revealed a paraaortic mass which was reconfirmed by ultrasound of abdomen. Laparotomy revealed a mesenteric lymph node that was removed. Histopathologically it was diagnosed as a case of CASTLEMAN'S DISEASE which is a rare cause of PUO. On removal of the lymph node, the patient improved dramatically. Key words: Castleman's disease; PUO DOI: 10.3329/bsmmuj.v2i2.4764 BSMMU J 2009; 2(2): 85-87